Digital Activism and Islamic Political Mobilization Among Millennial Muslims in the Election Contest - Rizal Al Hamid; Novian Widiadharma (Manunggal Halim Jaya, 2026)
The rapid development of digital technology has transformed patterns of political participation in contemporary democratic societies, including within Muslim communities. In recent years, Islamic digital activism has increasingly emerged through social media platforms such as TikTok, Instagram, X, and YouTube, which function not only as spaces for religious expression but also as instruments of political mobilization during electoral contestation. Muslim millennials, as digital natives, occupy a strategic position in shaping and disseminating Islamic political narratives in online public spheres. This study aims to analyze how digital activism influences Islamic political mobilization among Muslim millennials in electoral politics. Using a qualitative approach with digital ethnography methods, this research collects data through social media observation, online discourse analysis, and interviews with Muslim millennial users actively engaged in political content. The findings reveal that social media has transformed conventional Islamic political mobilization into a network-based and emotionally driven movement characterized by viral narratives, religious symbolism, and influencer-centered campaigns. Furthermore, digital activism strengthens identity-based political participation while simultaneously intensifying political polarization in online spaces. Theoretically, this study contributes to the development of digital political Islam discourse by integrating theories of connective action, cyber politics, and contemporary Islamic activism within the context of electoral democracy.